OPTIMIZING HUMAN RESOURCE DEVELOPMENT THROUGH INTEGRATED EDUCATION AND TRAINING PROGRAMS - Jubaidi, Didi; Khoirunnisa (Pojok Publisher, 2024)
Human Resource Development (HRD) is a key element in enhancing the competitiveness and productivity of an organization or country. Education and training play a central role in this process, as they not only equip individuals with the necessary knowledge and skills but also aid in personal and professional development. This study aims to analyze the basic concepts and definitions of HRD, as well as its vital role in achieving organizational goals. This research is a library research study that seeks to explore and analyze various literature sources related to the concept of Human Resources (HR) and its development within the organizational context. The findings also reveal that well-designed training programs, tailored to the specific needs of both the organization and the individual, are more likely to enhance performance and productivity.